2022
DOI: 10.3390/pathogens11030314
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Persistence, and Clearance of Anal Human Papillomavirus among Men Who Have Sex with Men in China: An Observational Cohort Study

Abstract: (1) Background: We conducted a prospective observational cohort study to measure incidence, persistence, and clearance of anal human papillomavirus (HPV) among men who have sex with men (MSM) in China. (2) Methods: MSM were recruited in Guangzhou, Shenzhen and Wuxi, China in 2017. A tablet-based questionnaire was used to collect sociodemographic and behavioral characteristics. An anal brush sample was collected for HPV testing and genotyping. Participants were followed up 12 months after enrolment. (3) Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
3
2
Order By: Relevance
“…Low-risk HPV genotypes have been proven to be attributed to genital warts and other lesions ( 26 ). High incidence and persistence rates were observed for anal HPV 6 and 42 among low-risk genotypes in this study, which are similar to the patterns found in a previous study ( 12 ). The highest persistence rate of HPV 6 in a large cohort study in Liuzhou, China was among low-risk genotypes ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Low-risk HPV genotypes have been proven to be attributed to genital warts and other lesions ( 26 ). High incidence and persistence rates were observed for anal HPV 6 and 42 among low-risk genotypes in this study, which are similar to the patterns found in a previous study ( 12 ). The highest persistence rate of HPV 6 in a large cohort study in Liuzhou, China was among low-risk genotypes ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…Zhou et al. investigated the natural history of HPV infection, including persistence rates ( 12 ). These studies with a continuous concern focus on HPV infection at the anus, but a few publications have reported on the natural history of penile HPV in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Around half of the participants had at least one type of HPV infection persistent after a year. The clearance rate was lower than that in Zhou's study among MSM in Guangzhou, Shenzhen, and Wuxi, China (147 cases/100 personyears) [16], which had a HIV prevalence of 7.1%. The clearance rate was higher than that of Videla's study among HIV-positive men in Spain (12.6 cases/100 person-years in MSM and 18.4 in MSW) [18].…”
Section: Discussioncontrasting
confidence: 69%
“…The incidence rate in our study was similar to a cohort study in America (21.3 cases/100 person-years) [14], higher than a South African study (2.9 cases/100 person-years) [15], and lower than a South-East Asian study (34.1 cases/100 person-years) [8]. We also found that the incidence rate among HIV-positive homosexual men in this study was lower than that of MSM in Guangdong, China (29.6 vs. 37.6 cases/100 person-years) [16], which had a younger study population. The incidence rate of HPV16 and HPV18 were lower than those of HIV-negative MSM in Xinjiang, China (2.3 vs. 10.6 and 1.4 vs. 5.2 per 100 person-years) [17].…”
Section: Discussioncontrasting
confidence: 62%
“…Cervical cancer, the fourth most common malignant tumor in women, with an incidence of 8.4/100.000 women/year in highincome countries [3], has virtually no other etiology than persistent HPV infection sustained by high-risk genotypes [4,5]. The burden of HPV-related diseases affects men too, as high-risk HPV genotypes are also associated with oropharyngeal, penile, and anal cancer [6,7], whose incidences, in high-income countries, have been estimated at 3.28, 0.66, and 0.74/100.000 men/year, respectively [3]. The most comprehensive systematic review on males-conducted in 2014-found a prevalence of HPV among European males of 12.5% in the general population and 30.9% in high-risk groups [8].…”
Section: Introductionmentioning
confidence: 99%